Unwelcome Companions: Loneliness Associates with the Cluster of Pain, Fatigue, and Depression in Older Adults. (February 2021) - Powell, Victoria D.; Abedini, Nauzley C.; Galecki, Andrzej T.; Kabeto, Mohammed; Kumar, Navasuja; Silveira, Maria J.
Objective: Pain, fatigue, and depression commonly co-occur as a symptom cluster in pathological inflammatory states. Psychosocial stressors such as loneliness may lead to similar states through shared mechanisms. We investigated the association of loneliness with pain, fatigue, and depression in older adults.Methods: Using Health and Retirement Study data ( N  = 11, 766), we measured cross-sectional prevalence of frequent, moderate to severe pain; severe fatigue; depressive symptoms; and co-occurrence of symptoms surpassing threshold levels (i.e., symptom cluster). Logistic regression models evaluated associations with loneliness.Results: Pain, fatigue, and depression were reported in 19.2%, 20.0%, and 15.3% of the total sample, respectively. The symptom cluster was seen in 4.9% overall; prevalence in lonely individuals was significantly increased (11.6% vs. 2.3%, p  < .0001). After adjusting for demographic variables, loneliness associated with the symptom cluster (adjusted OR = 3.39, 95% CI = 2.91, 3.95) and each symptom (pain adjusted OR = 1.61, 95% CI = 1.48, 1.76; fatigue adjusted OR = 2.02, 95% CI = 1.85, 2.20; depression adjusted OR = 4.34, 95% CI = 3.93, 4.79).Discussion: Loneliness strongly associates with the symptom cluster of pain, fatigue, and depression. Further research should examine causal relationships and investigate whether interventions targeting loneliness mitigate pain, fatigue, and depression.